Analysis of Cyanide Acid Content in Cassava (Manihot esculenta) Based on Storage Time - Ria Lumbantobing; Mery Napitupulu; Minarni R. Jura (Jurnal Akademika Kimia, 2019)
Cassava is a tuber of cassava plants which is a source of carbohydrates that can be consumed as food and as snack foods such as chips. However, cassava and the leaves contain cyanide acid (HCN) which is dangerous for the human when consumed in excess. Cyanide acid reduction can be done by washing as well as immersion because of its volatile nature. The aim of this research is to investigate the difference of cyanide acid (HCN) content on peeled and unpeeled cassava with the variation of storage time 0, 2, 4, 6, and 8 days. A preliminary test was done to know the existence of cyanide acid (HCN) in cassava. Method analysis of cassava was titrated with the NH4CNS solution using the argentometric principle of the Volhard method. The results showed that cyanide acid (HCN) content in peeled cassava was higher than unpeeled cassava which was 3.9, 4.7, 5.2, 5.6, and 6.0% respectively for shelled cassava and 3.9, 4.6, 5.1, 5.5, and 5.9% respectively for unpeeled cassava.